Examining the influence of user experience on functional value, satisfaction, and usage intention in OTT video platforms - Ya-Qin You; Han-Han Song; Yu-Liang Feng (PLoS ONE, 2026)
With the widespread availability of high-speed networks and smart devices, OTT video platforms have become a primary channel for entertainment and information. This study investigates how user experience (UX) dimensions—convenience/fluency, interaction, emotional experience, and service-quality experience—shape functional value, satisfaction, and usage intention in OTT video platforms. Based on survey data from 230 users (21 items measured on seven-point Likert scales), a PLS-SEM analysis was conducted using SmartPLS 3 with 5,000 bootstrap resamples. The model demonstrated acceptable fit (SRMR = 0.075) and acceptable predictive performance, with R² values of 0.522 for functional value, 0.760 for satisfaction, and 0.339 for usage intention, and Q² values indicating moderate-to-high predictive relevance. Results show that convenience/fluency positively influences functional value, satisfaction, and usage intention. Interaction exerts a direct positive effect on usage intention but not on functional value or satisfaction. Emotional experience enhances functional value, satisfaction, and usage intention, with satisfaction partially mediating its effect on intention. Service-quality experience positively influences functional value and satisfaction but does not show a significant direct effect on usage intention. Its association with usage intention appears to operate indirectly through evaluative pathways. Furthermore, functional value positively influences satisfaction but does not show a significant direct effect on usage intention, whereas satisfaction serves as a significant predictor of usage intention. These findings clarify the UX-driven pathways underlying the adoption of OTT video platforms and explain why service quality and functional value alone may not translate into usage intention without satisfaction. From a practical perspective, OTT platforms should prioritize seamless performance, emotionally engaging content, and interactive features, while maintaining reliable service delivery as a basic condition for strengthening functional value and satisfaction.